Glial‐cell‐mediated re‐induction of the blood‐brain barrier phenotype in brain capillary endothelial cells: A differential gel electrophoresis study. Issue 7 (5th April 2013) - Deracinois, Barbara; Pottiez, Gwënaël; Chafey, Philippe; Teerlink, Tom; Camoin, Luc; Davids, Mariska; Broussard, Cédric; Couraud, Pierre‐Olivier; Dehouck, Marie‐Pierre; Cecchelli, Roméo; Karamanos, Yannis; Flahaut, Christophe
<x xml:space="preserve">Abstract</x> In the neurovascular unit, brain microvascular endothelial cells develop characteristic barrier features that control the molecular exchanges between the blood and the brain. These characteristics are partially or totally lost when the cells are isolated for use in in vitro blood‐brain barrier (BBB) models. Hence, the re‐induction of barrier properties is crucial for the relevance of BBB models. Although the role of astrocyte promiscuity is well established, the molecular mechanisms of re‐induction remain largely unknown. Here, we used a DIGE‐based proteomics approach to study endothelial cellular proteins showing significant quantitative variations after BBB re‐induction. We confirm that quantitative changes mainly concern proteins involved in cell structure and motility. Furthermore, we describe the possible involvement of the asymmetric dimethylarginine pathway in the BBB phenotype re‐induction process and we discuss asymmetric dimethylarginine's potential role in regulating endothelial function (in addition to its role as a by‐product of protein modification). Our results also suggest that the intracellular redox potential is lower in the in vitro brain capillary endothelial cells displaying re‐induced BBB functions than in cells with limited BBB functions.